The impact of religious certification on market segmentation and investor recognition - Alhomaidi, Asem; Hassan, M. Kabir; Hippler, William J.; Mamun, Abdullah (Journal of Corporate Finance, 2019)
We compare the performance of Islamic and conventional stock returns in Saudi Arabia in order to determine whether religious preferences can create segmented financial markets consistent with investor recognition effects. We sample the daily stock returns of all Saudi firms from September 2002 through 2015 and find Islamic stocks (recognized) have a broader investor base, are more liquid (Amihud, 2002) and exhibit lower idiosyncratic risk (Ang et al., 2006) than conventional (neglected) stocks, which support the segmentation of Islamic and conventional stocks in the Saudi market. Furthermore, the segmentation of Islamic stocks from less-recognized conventional stocks significantly affects how information is incorporated into asset prices in predominantly Islamic markets. Islamic stocks exhibit greater integration with local and global macroeconomic factors (Pukthuanthong and Roll, 2009) and have higher systematic turnover (Loughran and Schultz, 2005) than conventional stocks. Our results provide new evidence on the impact of the corporate decision to comply with religious and social norms on asset pricing in emerging markets, the evolving Islamic financial markets, and markets where other significant implicit, or cultural, barriers may exist.